Hubungan antara kadar fibrinogen plasma dengan ketebalan tunika intima media arteri karotis komunis pada diabetes melitus - , dr. Dwi Aryani, Prof. dr. Budi Mulyono, SpPK-K, MM ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Â  Diabetes mellitus is a global health problem due to the increase of its prevalence, morbidity and mortality. Data from WHO 1997 show an increase prevalence of diabetes are the countries of Southeast Asia, including Indonesia. Diabetes mellitus has chronic complications such as microvascular and macrovascular, macrovascular complications such as atherosclerosis The abnormal metabolic state that accompanies diabetes causes arterial dysfunction. Relevant abnormalities include chronic hyperglycemia, dyslipidemia and insulin resistance. This factors render the arteries susceptible to atherosclerosis. The increase carotid communist IMT examined using USG has become a standard for assessing atherosclerosis and recommended by the American Heart Association as a non-invasive assessment of cardiovascular risk. Fibrinogen levels have a role in atherosclerosis. This study was cross-sectional design to examine the association between plasma fibrinogen with carotid communist IMT in patients with DM. Subjects were patients with DM based on criteria PERKENI coming to Dr DR. Sardjito Yogyakarta selected sequentially and fulfill inclusion - exclusion criteria. Examination of fibrinogen by Clauss method, whereas the carotid communist artery IMT T examined using ultrasound. There is a positive correlation between plasma fibrinogen with carotid communist IMT in type 2 diabetes mellitus, r = 0.36 and p = 0.021. Positive correlation between age and carotid IMT with r = 0.314 and p = 0.048.